PENGARUH DIRECT MAIL DAN TELEMARKETING TERHADAP KEPUTUSAN PEMBELIAN PAKET UMRAH RAKA TOURS AND TRAVEL (Survey Terhadap Pengguna Paket umrah Raka Tours and Travel) - Dewi, Nurmala; Purnama, Ridwan (Universitas Pendidikan Indonesia, 2013)
One type of tourism has great potential. Umrah and Hajj is a popular type of religious tourism in Indonesia. The potential is rated high because the majority of Indonesia's population is Muslim. Given this also emerging cooperation between Indonesia and Saudi Arabia as a tourist destination more closely. One of them with the cooperation of the travel-travel in Indonesia with travel that is in Saudi Arabia. This of course affects the number of trips efforts in several major cities in Indonesia, one of which the city of Bandung.One travel agency Bandung is Raka Tours and Travel. Raka Tours and Travel is a BPW (Travel Bureau), which is engaged in servicing a variety of travel needs, such as the sale of air transportation tickets, hotel vouchers, travel packages, various services of travel documents, MICE and religious journey that umrah and hajj. Raka Tours umrah package sales decreased from 2010 to 2011. The sales decline Raka Tours umrah package is reached -14.55%. Direct marketing especially in direct mail and telemarketing is one of the strategies that can be used to increase sales.In this regard it is done research on the effect of direct mail and telemarketing to purchasing decision umrah package. Step - step Direct Marketing consists of direct mail (direct mail) and telemarketing (selling over the phone).Type of research is descriptive and verification methods used are cross sectional method with the sample size using the formula iteration, the obtained sample size of 110 respondents. The analysis technique used is multiple linear regression analysis with SPSS for windows 18:00. Based on the test results obtained by statistical findings of direct marketing in which all variables have an influence on purchase decisions that direct mail and telemarketing, it showed 65.15% have an influence on the purchase decision, while the remaining 34.85% influenced by other variables. Thus, the direct mail and telemarketing have a strong influence in influencing purchasing decisions Raka umrah package tours and Travel.